2010
DOI: 10.1111/j.1749-7345.2010.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of First-prey Type and Number on Survival and Growth of Intensively Cultured Spotted Seatrout, Cynoscion nebulosus (Sciaenidae), Larvae

Abstract: Five test diets – 20, 10 rotifers/mL/d, 5 rotifers/mL/d + 3 nauplii/mL/d, 5 and 8 nauplii/mL/d – were used to examine the effect of Acartia tonsa nauplii and a small strain of rotifers on survival, myotome height, notochord length, and condition (myotome height/notochord length) of spotted seatrout, Cynoscion nebulosus, larvae through 6‐d posthatch (PH). Diet did not affect survival. Larvae fed 5 and 8 nauplii/mL or 5 rotifers + 3 nauplii were longer, taller, and in better condition than larvae fed either 10 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Larvae fed copepods also tended to be more uniform in size than those fed rotifers. Despite the positive effects of copepods on early growth, Lemus et al (2010) concluded that the benefits of copepods are currently outweighed by the cost and difficulty in providing a sufficient number of copepod nauplii to support largescale culture.…”
Section: Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae fed copepods also tended to be more uniform in size than those fed rotifers. Despite the positive effects of copepods on early growth, Lemus et al (2010) concluded that the benefits of copepods are currently outweighed by the cost and difficulty in providing a sufficient number of copepod nauplii to support largescale culture.…”
Section: Feedingmentioning
confidence: 99%
“…Nauplii of calanoid copepods, which are considered superior to rotifers and brine shrimp, were offered during early feeding (through day 6) of seatrout larvae by Lemus, Blaylock, Apeitos, and Lotz (2010). The inclusion of copepod nauplii did not increase survival, but larvae fed either copepods alone or in combination with rotifers were larger and in better condition than those fed rotifers alone, perhaps because copepods provided a nutritional supplement.…”
Section: Feedingmentioning
confidence: 99%
“…También se ha demostrado que el uso de análogos de la hormona liberadora de gonadotropina (LHRHa), administrada por vía oral en dosis de 1 mg kg -1 de pez, induce efectivamente al desove (Thomas & Boyd 1989), así como también se han obtenido desoves naturales con control de temperatura y fotoperiodo (Wisner et al 1996). Por otro lado, la cría de larvas de esta especie ha recibido gran atención y ha sido estudiada con enfoques fisiológicos (Banks et al 1991), metabólicos (Wuenschel & Werner 2004, Wuenschel et al 2004, alimentarios, como la determinación de la densidad del alimento óptima en los primeros días del cultivo larvario (Lemus et al 2010) y el efecto de la densidad sobre el comportamiento agresivo (canibalismo) (Manley et al 2014). …”
Section: Introductionunclassified
“…One of the major obstacles is that once the larvae are released into rearing ponds, water quality parameters such as temperature and salinity are subject to ambient environmental fluctuations that may not be suitable for larval grow-out and survival (McDonald et al 2013). In addition to environmental issues, another bottleneck to marine fish production is the availability of nutritionally replete feeds, especially during the early larval stages (Lemus et al 2010). Many marine species are reared by using a combination of rotifers, brine shrimp Artemia spp.…”
mentioning
confidence: 99%
“…Many marine species are reared by using a combination of rotifers, brine shrimp Artemia spp. nauplii, and copepods (Palmtag et al 2006;Seychelles et al 2009;Lemus et al 2010;Lindley et al 2011). Arnold et al (1978) developed the first tank-rearing protocol for larval Spotted Seatrout, which included algae, rotifers, and Artemia.…”
mentioning
confidence: 99%